401 Phase 1/2 study of novel HER2-targeting, TLR7/8 immune-stimulating antibody conjugate (ISAC) BDC-1001 with or without immune checkpoint inhibitor in patients with advanced HER2-expressing solid tumors. (9th November 2020) - Sharma, Manish; Dumbrava, Ecaterina Ileana; Carvajal, Richard; Catenacci, Daniel; Emens, Leisha; Hanna, Glenn; Juric, Dejan; Kang, Yoon-Koo; Lee, Jeeyun; Lee, Keun-Wook; Li, Bob; Moore, Kathleen; et al.
Abstract : Background: In spite of advances made in the management of patients with HER2-expressing or -driven solid tumors, there remains a significant unmet need for novel approaches to improve patient outcomes. Intratumoral delivery of antitumor antibodies and immunostimulatory adjuvants such as toll-like receptor (TLR)7/8 agonists has been shown to activate tumor resident antigen-presenting cells (APCs), driving uptake, processing, and presentation of tumor neoantigens to T cells that mediate antitumor immunity. BDC-1001 is delivered systemically and has demonstrated superior preclinical biology. This novel ISAC consists of an investigational biosimilar of the humanized monoclonal antibody trastuzumab chemically conjugated to a TLR7/8 agonist with a non-cleavable linker. BDC-1001 activates human myeloid APCs in addition to retaining antibody-mediated effector functions such as antibody-dependent cellular cytotoxicity/phagocytosis (ADCC/ADCP). Studies in trastuzumab-resistant xenograft models and syngeneic tumor models indicate that HER2-targeted ISACs elicit potent and durable immune-mediated antitumor efficacy, leading to complete tumor regression in a TLR- and Fc receptor-dependent manner. 1 2 Importantly, BDC-1001 did not induce interstitial lung disease, cytokine release syndrome, or thrombocytopenia in non-human primate studies. A four-part phase 1/2, first-in-human study has been initiated that evaluates BDC-1001 with or without (±) an immune checkpoint inhibitor targeting PD-1 in patients with HER2-expressing or HER2-amplified advanced/metastatic solid tumors. Methods: This dose-escalation and dose-expansion study is enrolling up to 390 patients with HER2-expressing (IHC2+ or 3+ protein, irrespective of gene amplification) or HER2-amplified (by in situ hybridization or next-generation sequencing) advanced solid tumors. Primary objectives of the dose-escalation phase are to define safety and tolerability and determine the recommended phase 2 dose of BDC-1001 as monotherapy (Part 1) and in combination with an immune checkpoint inhibitor (Part 2). Part 2 is planned to start once BDC-1001 safety data are available. Primary endpoints include incidence of 1) adverse events and serious adverse events; 2) dose-limiting toxicities within a 3+3 design; and 3) potential immune-related toxicities. The dose-expansion portion of the trial will evaluate preliminary antitumor activity of BDC-1001 alone (Part 3) and in combination with an immune checkpoint inhibitor (Part 4). Secondary objectives will evaluate pharmacokinetic parameters and pharmacodynamic biomarkers in tumor tissue and in peripheral blood associated with drug exposure. These exploratory studies will help elucidate the mechanism of action and seek to identify biomarkers associated with BDC-1001 biological activity with or without immune checkpoint inhibitor. This global study is currently recruiting patients. Results: N/A Conclusions: N/A Trial Registration: ClinicalTrials. gov (NCT04278144 ). Ethics Approval: The study and the protocol were or will be approved by the Institutional Review Board or ethics committee at each site. Consent: N/A References: Ackerman, et al. TLR7/8 immune-stimulating antibody conjugates elicit robust myeloid activation leading to enhanced effector function and anti-tumor immunity in pre-clinical models. Cancer Res . 2019:79 [13 Suppl]:Abstract 1559. Ackerman, et al. HER2-targeting TLR7/8 immune-stimulating antibody conjugates elicit robust myeloid activation and anti-tumor immune responses in a TLR- and FcR- dependent manner. J Immunother Cancer 2019;7 :283